Molecular magnetic resonance imaging accurately measures the antifibrotic effect of EDP‐305, a novel farnesoid X receptor agonist. Issue 7 (21st May 2018) - Erstad, Derek J.; Farrar, Christian T.; Ghoshal, Sarani; Masia, Ricard; Ferreira, Diego S.; Chen, Yin‐Ching Iris; Choi, Ji‐Kyung; Wei, Lan; Waghorn, Phillip A.; Rotile, Nicholas J.; Tu, Chuantao; Graham‐O'Regan, Katherine A.; et al.
Abstract : EDP‐305, a novel FXR agonist, reduced fibrosis progression in rat BDL and mouse CDAHFD models of hepatic injury. Changes in hepatic fibrosis were measurable with molecular magnetic resonance imaging of collagen and oxidized collagen. Abstract : We examined a novel farnesoid X receptor agonist, EDP‐305, for its antifibrotic effect in bile duct ligation (BDL) and choline‐deficient, L‐amino acid‐defined, high‐fat diet (CDAHFD) models of hepatic injury. We used molecular magnetic resonance imaging with the type 1 collagen‐binding probe EP‐3533 and the oxidized collagen‐specific probe gadolinium hydrazide to noninvasively measure treatment response. BDL rats (n = 8 for each group) were treated with either low or high doses of EDP‐305 starting on day 4 after BDL and were imaged on day 18. CDAHFD mice (n = 8 for each group) were treated starting at 6 weeks after the diet and were imaged at 12 weeks. Liver tissue was subjected to pathologic and morphometric scoring of fibrosis, hydroxyproline quantitation, and determination of fibrogenic messenger RNA expression. High‐dose EDP‐305 (30 mg/kg) reduced liver fibrosis in both the BDL and CDAHFD models as measured by collagen proportional area, hydroxyproline analysis, and fibrogenic gene expression (all P < 0.05). Magnetic resonance signal intensity with both EP‐3533 in the BDL model and gadolinium hydrazide in the CDAHFD model was reduced with EDP‐305 30 mg/kg treatment ( P < 0.01). Histologically, EDP‐305 30 mg/kg halted fibrosis progression in the CDAHFD model. Conclusion : EDP‐305 reduced fibrosis progression in rat BDL and mouse CDAHFD models. Molecular imaging of collagen and oxidized collagen is sensitive to changes in fibrosis and could be used to noninvasively measure treatment response in clinical trials. ( Hepatology Communications 2018;2:821‐835)